God and the reach of reason - Wielenberg, Erik J (Cambridge University Press, 2013)
Plato tells us that Socrates, facing execution in 399 B.C., declared that “the one aim of those who practice philosophy in the proper manner is to practice for dying and death.”1 Writing nearly two thousand years later, Michel de Montaigne remarked that “all the wisdom and reasoning in the world boils down finally to this point: to teach us not to be afraid to die